Membangun Budaya Literasi Masyarakat Pekon Sukananti Kecamatan Way Tenong Kabupaten Lampung Barat melalui Perpustakaan Desa dan Taman Baca Masyarakat - Marlena Marlena; Irwandani Irwandani; Rahma Diani (Smart Society, 2021)
This service aims to describe the causes of the low interest in reading in the community, especially the young generation of school age in the village of Sukananti; diagnosing various causes of low interest in reading in the Sukananti village community; and designing a program of reading activities as an effort that can encourage people to want to read so that a literacy culture can be realized, especially for the young generation of school age in Sukananti village, Way Tenong district, West Lampung Regency through the provision of village libraries and community reading parks (TBM). The approach used in the implementation of this program and research is a qualitative approach in the form of a case study by examining events or events related to reading interest and literacy culture. Data collection techniques through observation, interviews, and data recording. Data analysis techniques are carried out through the presentation, analysis, description, and presentation of data related to the reading interest and culture of the community. In this case, to be able to build and increase interest in reading in order to foster a literacy culture, it is necessary to carry out various strategies and programs that can reach all levels of society, such as the provision of IT-based village library facilities, procurement of community reading parks, and can be pursued through the involvement of KKN students to teach. read and write for two to three months, and it is necessary to cooperate with the nearest school to provide access for the dropout community to get the opportunity to learn.